2016
DOI: 10.1111/1471-0528.14133
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged latency of preterm prelabour rupture of membranes and neurodevelopmental outcomes: a secondary analysis

Abstract: Objective To determine whether prolonged latency after preterm prelabour rupture of membranes (PPROM) is associated with an increased risk for adverse neurodevelopmental outcomes.Design This is a secondary analysis of the randomised controlled trial of magnesium sulphate for the prevention of cerebral palsy. Setting Multicentre trial.Population A total of 1305 women with PPROM were analysed, 1056 of whom had an interval of <3 weeks between diagnosis and delivery and 249 of whom had an interval of ≥3 weeks betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Ramsey 38 reported that the expectant management in PPLROM allowed prolongation of pregnancy benefited neonatal outcome, though increased the risk of chorioamnionitis and associated maternal and neonatal morbidity. Drassinower 39 has also reported that delivery at later gestational age was associated with improved prognosis for the baby. When the per week effect of latency was combined with the protective effect of each additional week of gestational age, the adjusted results pointed towards a slight (but not significant) net benefit from each additional week in utero.…”
Section: Discussionmentioning
confidence: 98%
“…Ramsey 38 reported that the expectant management in PPLROM allowed prolongation of pregnancy benefited neonatal outcome, though increased the risk of chorioamnionitis and associated maternal and neonatal morbidity. Drassinower 39 has also reported that delivery at later gestational age was associated with improved prognosis for the baby. When the per week effect of latency was combined with the protective effect of each additional week of gestational age, the adjusted results pointed towards a slight (but not significant) net benefit from each additional week in utero.…”
Section: Discussionmentioning
confidence: 98%
“…We thank Roberts et al for their interest in our study 1,2 and for the opportunity to clarify that our study does not show 'that there is a net disadvantage to additional time in utero'. We presented the unadjusted results, which show that motor and mental Bayley scores <70, <85, and mean motor and mental Bayley scores were similar in the <3 weeks and ≥3 weeks groups.…”
Section: Sirmentioning
confidence: 89%
“…They raise concerns about the wide variation between the guidelines and highlight the higher thromboprophylaxis rates in the UK, whilst acknowledging the reduced maternal mortality associated with venous thromboembolism (VTE) in the UK in recent years. 2 The RCOG VTE prevention guidance was updated in 2015, 3 and the impact on thromboprophylaxis rates is as yet unknown. The key changes include alterations to thrombotic risk factors and modifications to prophylaxis recommendations per aggregate risk factors.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Roberts et al. for their interest in our study and for the opportunity to clarify that our study does not show ‘that there is a net disadvantage to additional time in utero’. We presented the unadjusted results, which show that motor and mental Bayley scores <70, <85, and mean motor and mental Bayley scores were similar in the <3 weeks and ≥3 weeks groups.…”
mentioning
confidence: 91%